Zygomatico-maxillary Reconstruction with Computer-aided Manufacturing of a Free DCIA Osseous Flap and Intraoral Anastomoses. (February 2017) - Roy, Andrée-Anne; Efanov, Johnny I.; Mercier-Couture, Geneviève; Chollet, André; Borsuk, Daniel E.
Abstract : Summary: Craniomaxillofacial reconstruction using virtual surgical planning, computer-aided manufacturing, and new microsurgical techniques optimizes patient-specific and defect-directed reconstruction. A 3D customized free deep circumflex iliac artery (DCIA) flap with intraoral anastomoses was performed on a 23-year-old man with a posttraumatic right zygomatico-maxillary defect with failure of alloplastic implant reconstruction. An osseous iliac crest flap was sculpted based on a customized 3D model of the mirror image of the patient's unaffected side to allow for perfect fit to the zygomatico-maxillary defect. An intraoral dissection of the facial artery and vein was performed within the right cheek mucosa and allowed for end-to-end microvascular anastomoses. 3D preoperative planning and customized free DCIA osseous flap combined with an intraoral microsurgical technique provided restoration of facial esthetics and function without visible scars. In cases where zygomatico-malar reconstruction by alloplastic material fails, a customized free DCIA osseous flap can be designed by virtual surgical planning to restore facial appearance and function.